2010
DOI: 10.1089/scd.2009.0439
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Bone Marrow-Derived Stromal Stem Cells Unmask Latent Malignancy

Abstract: Neoplastic epithelia may remain dormant and clinically unapparent in human patients for decades. Multiple risk factors including mutations in tumor cells or the stromal cells may affect the switch from dormancy to malignancy. Gene mutations, including p53 mutations, within the stroma of tumors are associated with a worse clinical prognosis; however, it is not known if these stromal mutations can promote tumors in genetically at-risk tissue. To address this question, ApcMin/+ and Apc Min/+ Rag2 −/− mice, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 51 publications
0
32
0
1
Order By: Relevance
“…Although controversial [68], such mutations have been reported in cancer-associated stromal cells, and have been proposed as responsible for the shift toward a cancer-permissive stromal environment [69]. Stromal cells carrying TP53 lossof-function enhance mammary tumor development in cancerprone mice, and promote the growth of breast cancer xenotransplants to a higher extent than in non-mutated counterparts [70,71]. Interestingly, fibroblasts showing a down-regulation of a tumor suppressor (e.g.…”
Section: Specific Genomic Alterations Contribute To the Pro-inflammatmentioning
confidence: 99%
“…Although controversial [68], such mutations have been reported in cancer-associated stromal cells, and have been proposed as responsible for the shift toward a cancer-permissive stromal environment [69]. Stromal cells carrying TP53 lossof-function enhance mammary tumor development in cancerprone mice, and promote the growth of breast cancer xenotransplants to a higher extent than in non-mutated counterparts [70,71]. Interestingly, fibroblasts showing a down-regulation of a tumor suppressor (e.g.…”
Section: Specific Genomic Alterations Contribute To the Pro-inflammatmentioning
confidence: 99%
“…However, genetic alteration of tumor stromal cells (CAFs) under the influence of the TME, which is known to cause tumor development and progression, has not received much attention. Although several studies have demonstrated the association of certain CAF mutations with carcinomas (21-23), these mutations were only associated with the initiation of epithelial cell carcinomas (19,24) and their role in their own malignant transformation remains to be elucidated. Stromal cells recruited to the TME are termed 'non-tumor' cells and are known to play a role in tumor progression or suppression.…”
Section: Introductionmentioning
confidence: 99%
“…Mice deficient in tumor necrosis factor alpha (TNF) and IFNAR1 have been demonstrated to have an elevated incidence of MCA-induced sarcomas (21) (22), indicating that these two cytokines are critical players in cancer immunosurveillance. However, the role of TNF in tumor dormancy remains controversial due to contradictory findings in studies of tumor dormancy (23, 24). Here, equilibrium was not altered in different cohorts of MCA treated mice given neutralizing/blocking mAbs to either TNFα or the type I IFN receptor (Fig.…”
Section: Resultsmentioning
confidence: 99%